The Guide in Uighur Fairytales: Bovay - Fatoş Yalçınkaya (Uluslararası Halkbilimi Araştırmaları Dergisi)
Tales are products of a society's cultural memory. Fairy tales that establish a connection between the past and the future, especially magic tales, carry traces of the religious belief system to which the society belongs. Some of the supernatural beings in tales are the reflection of the belief system in the mythical period. Magic tales contain many supernatural beings, types and motifs. One of the extraordinary helpers in the tales of the Turkish world is the guiding, white-bearded, old, wise person. One of these characters, Bovay, is a type with divine characteristics. This character, who bears the traces of the mythical period, is a white-bearded man who helps pure-hearted people who have gone through various trials. With the Turks' acceptance of Islam, this person continues to live by integrating with the Hızır type. Bovay, over time, finds himself in narratives as Hızır Bovay and more recently as Hızır. In tales, when the hero sets out on a journey, he encounters this divine figure at various stages of the journey. While classifying the characters in the tale, Uyghur folklorists have examined Hızır and the perizats under the title of divine obraz. Usually, the extraordinary in fairy tales is solved with the help of these characters. For this reason, they are indispensable in fairy tales. Bovay is a guide. He is the person who helps the hero, directs him to the right path, and sometimes brings him a divine message or a magical object. Bovay is a saint who carries a divine message and a sacred relic (magical objects). In our study, we will focus on the function of Bovay, the divine object in Uyghur magic tales, in tales. Firstly, a literature review was conducted on Uyghur tales published in Turkey and East Turkestan.The fairy tale texts were selected from a total of 872 fairy tale texts. The magic tales used in our text-centered study were taken from the serial books published by Şincan Halk Neşriyatı between 1979-1988 and 1980-1997.The sample of the study was limited to Uyghur magic tales.